Alveolar regeneration through a Krt8+ transitional stem cell state that persists in human lung fibrosis - Maximilian Strunz (Nature Portfolio, 2020)
Injury repair is characterized by the generation of transient cell states important for tissue recovery. Here, the authors present a single cell RNA-seq map of recovery from bleomycin lung injury in mice and uncover a Krt8+ transitional stem cell state that precedes the regeneration of AT1 cells and persists in human lung fibrosis.